Răspunsuri

2014-05-27T21:47:51+03:00

2x - x² - 6 + 3x - (x² - 25) = -2x² + 12x - 5x + 5

2x - x² - 6 + 3x - x² + 25 = - 2x² + 12x - 5x + 5

Trecem numerele pe o parte și termenii cu x pe cealaltă parte.

2x - x² + 3x - x² + 2x² -12 x + 5x = + 5 + 6 - 25

-2 x = - 14  (înmulțim cu -1)

2x = 14 => x = 14 supra 2 = 7 .

Sper să îți fie de folos! :*


2014-05-27T21:48:13+03:00
2x-6- x^{2}  x^{2} +2x-( x^{2} +5x-25-5x)=-2x( x^{2} -x-6x+6)

2x-6- x^{2} +2x- x^{2} -5x-25-5x=-2 x^{3} +2 x^{2} +12-12 .. sper sa te ajute.. ma depaseste.. :D